Adolescent E-cigarette use trajectories and subsequent alcohol and marijuana use. (April 2020) - Park, Eunhee; Livingston, Jennifer A.; Wang, Weijun; Kwon, Misol; Eiden, Rina D.; Chang, Yu-Ping
Highlights: During adolescence, three developmental patterns of e-cigarette use were identified. Increasing use of e-cigarettes is associated with alcohol intoxication. Increasing use of e-cigarettes is associated with marijuana use. Abstract: Introduction: As electronic cigarette (e-cigarette) use has become more prevalent among adolescents, there is a growing body of evidence linking e-cigarette use to the initiation of other substances. Whether there is a threshold level of e-cigarette use that is predictive of other substance use is unknown. The current study examines patterns of e-cigarette use over time and determines whether different patterns of early adolescent e-cigarette use are concurrently and prospectively associated with alcohol and marijuana use in late adolescence. Method: Eight hundred and one adolescents (13–15 years old at baseline recruitment) completed five on-line surveys over a two-year period. Latent class growth analysis was used to model different developmental courses of e-cigarette, alcohol (drinking to intoxication), and marijuana use. Logistic regression was used to test the association between e-cigarette use trajectory patterns and alcohol and marijuana use trajectories. Results: Three developmental courses of e-cigarette use were identified: 1) high and increasing, 2) low and increasing, and 3) never. Compared to adolescents who had never used e-cigarettes, those in the other two groups were more likely to have been intoxicated and to be in the moderate and increasing marijuana use group. Conclusion: Both high and low levels of e-cigarette use patterns are associated with increasing use of other substances (alcohol and marijuana use) over time. Findings highlight the need for early intervention and prevention of e-cigarette use among adolescents.